Melatonin-induced development of adventitious roots, biosynthesis of secondary cell products and greener synthesis of silver nanoparticles for biological activities using Indigofera heterantha - Ullah, Irfan (2023)
Indigofera heterantha is a medicinal shrub of the family Fabaceae that naturally produces pharmaceutically important polyphenolics and at the verge of extinction due to ruthless exploitation. The adventitious roots provide bases for the conservation of endangered plants by decreasing pressure on their wild populations and help in the large-scale production of pharmacologically important secondary metabolites. The main objective of the current study was to establish a feasible protocol for adventitious roots and to investigate the effect of melatonin on the biosynthesis of biomass, secondary cell products, and greener synthesis of silver nanoparticles (AgNPs) for various biological activities. Melatonin is an important growth promoter and plays a key role in plant defense that can be used as elicitors for large-scale production of secondary metabolites. Different concentrations of melatonin revealed that 1.5 mg l−1 melatonin was effective for the biosynthesis of maximum biomass during log phases of growth kinetics. The same melatonin concentration enhanced total phenolics content (TPC; 68.28 mg/g-DW), total flavonoids content (TFC; 24.34 mg/g-DW), total phenolics production (TPP; 153.63 g l−1), total flavonoids production (TFP; 54.80 g l−1), antioxidant activity and total secondary metabolites in adventitious roots. The melatonin-treated roots (300 mM) were able to produce maximum biogenic AgNPs, characterized by UV–vis spectroscopy (UV), scanning electron microscope (SEM), Fourier transform infrared (FTIR), and X-ray diffraction (XRD) and were used for various biological activities. These NPs displayed maximum antimicrobial activities and further revealed that AgNPs and aqueous root extract displayed higher cytotoxic activities. The protocol developed here provides an alternative strategy for germplasm conservation and melatonin proved to be one of the best elicitors for different activities and has the potential of scaling up by various pharmaceutical industrial applications.